Helping strategies in advice columns - Rayos, Nancy C. (2005)
This study sought to identify helping strategies used by advice columnists in responding to concerns presented by advice seekers using a qualitative-descriptive method of investigation. Thirty-five articles attributed to 7 advice columnists published in 4 newspapers and 2 magazines of national circulation were content analyzed guided by Young's (1998) Therapeutic Building Blocks. Results showed that advice columnists used solution-giving skills most frequently specifically giving advice/directives. It was concluded that advice columns have limited helping value and that advice in print cannot capture the fine nuances of helping.
Keywords: Advice columns -- Analysis; Advice columnists; Counseling